Papers of Andree Johnston-Bell - Johnston-Bell, Andree (1974)
Correspondence files of Andree Johnston-Bell, 1976-1982; Australasian antique collector, Nos. 17-20, 1974-1980 and the Australian antique collector, Nos. 21-23, 1981-1982.
Manuscript reference no. : MS 6742.
Andree Johnston-Bell is the retiring editor of Australian antique collector formerly Australasian antique collector.
Keywords: Johnston-Bell, Andree -- Correspondence; Editors -- Australia -- Correspondence; Antiques -- Periodicals; Editors